Energy-Conserved Hydrodynamic Lubricated Components with Wall Slippage - Xiaoxu Huang; Yongbin Zhang (International Journal of Rotating Machinery)
The hydrodynamic thrust slider and journal bearings as well as hydrodynamic lubricated gears with the merit of energy conservation by the wall slippage are reviewed. The principle for designing these hydrodynamic contacts is to artificially set the wall slippage on the stationary surface in the hydrodynamic inlet zone. To design the wall slippage on the moving surface in the hydrodynamic outlet zone can also give additional benefits. The technical merits of these mechanical components are the improved load-carrying capacity and the lowed friction coefficient, i.e., the energy conservation due to the wall slippage. Owing to the designed wall slippage, the carried load of the hydrodynamic step bearing can be increased by 200%~400% while its friction coefficient can be reduced by 50%~85%, and the load-carrying capacity of the hydrodynamic journal bearing can be increased by nearly 100% while at the same time, its friction coefficient can be reduced by more than 60%. For hydrodynamic lubricated gear contacts, by covering ultrahydrophobic or oilphobic coatings on the slower moving surface, the friction coefficient can be approaching to vanishing and the contact load-carrying capacity can be increased very significantly for large slide-roll ratios under medium or heavy loads.